Germany's Planned Public Investment Push: Fiscal Dilemmas and Missing Dimensions - Gerd Schwartz (CESifo Forum, 2022)
Germany's new coalition government, in place since December 2021, has called for a decade of "investment into the future," an ambitious public investment push, focused on achieving climate neutrality, fostering digitalization, advancing science and education, and improving infrastructure. Yet, the government has also committed to refraining from tax increases and returning to its fiscal anchor (a constitutionally mandated "debt brake" that has been suspended for 2020–2022), and it has not indicated cuts in other spending items that could make room for increased investments. How does this hang together? Part of the answer lies in doing as much as possible before the debt brake bites again in 2023, and part of it lies in scaling up existing extrabudgetary mechanisms to circumvent the self-imposed fiscal and budgetary confines. Yet, without a more comprehensive approach, one that combines innovations in infrastructure financing with a clear accounting of fiscal risks and significant reforms in public investment governance, the government's ambitious public investment push is likely to fizzle out.
Keywords: 330